2019
DOI: 10.1101/755934
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experience-dependent development of dendritic arbors in mouse visual cortex

Abstract: 17 65 processes. For the first time, we also establish Rem2 -a small GTPase previously implicated in 66 dendritic complexity in vitro and in Xenopus Laevis optic tectum [51, 53-55] -as an experience-67 dependent negative regulator of dendritic complexity in mammalian visual cortex. This work 68 demonstrates that Rem2 cell-autonomously regulates the arrangement of the basal dendrites: 69 neurons in which Rem2 has been deleted are less likely to exhibit a significant directionality and 70 sometimes exhibit abnor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 107 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…This also applies to the maturation of the dendritic processes because the dendritic architecture fundamentally determines the functional capacity of neurons. During early postnatal development significant dendritic process formation takes place in various brain areas (Kolb and Fantie, 1997) (Richards et al, 2020) and the formation and pruning of dendritic processes determine the density of the neural network in which individual neurons become embedded. Given the unique function and shape of the dendritic arbor, the integrity of the microtubule cytoskeleton and proper transport processes are crucial during dendritic process formation (Bramham and Wells, 2007; Penazzi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This also applies to the maturation of the dendritic processes because the dendritic architecture fundamentally determines the functional capacity of neurons. During early postnatal development significant dendritic process formation takes place in various brain areas (Kolb and Fantie, 1997) (Richards et al, 2020) and the formation and pruning of dendritic processes determine the density of the neural network in which individual neurons become embedded. Given the unique function and shape of the dendritic arbor, the integrity of the microtubule cytoskeleton and proper transport processes are crucial during dendritic process formation (Bramham and Wells, 2007; Penazzi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This also applies to the maturation of the dendritic processes because the dendritic architecture fundamentally determines the functional capacity of neurons. During early postnatal development significant dendritic process formation takes place in various brain areas (Kolb and Fantie, 1997) (Richards et al, 2020) and the formation and pruning of dendritic processes determine the density of the neural network in which individual neurons become embedded.…”
mentioning
confidence: 99%
“…In the visual cortex (VC) dendrite outgrowth is prominent from birth 22 , synapse formation is high from P7 23,24 , synaptic maturation begins ~P14 25 and circuit stabilization is achieved by ~P120 (Figure 1A). In neurotypical development Ptn has widespread expression throughout the brain, and prominent expression in upper cortical layers (Figure S1A-A').…”
Section: Ptn Expression Is Developmentally Regulated and Is Decreased...mentioning
confidence: 99%
“…To ask how Ptn expression correlates with important periods of synaptic development, we utilized a previously published astrocyte RiboTag RNA-sequencing dataset of the visual cortex 16 to determine the temporal profile of Ptn expression. In the visual cortex dendrite outgrowth is prominent from birth 17 , synapse formation is high from P7 18,19 , synaptic maturation begins ~P14 20 and circuit stabilization is achieved by ~P120 (Figure 1A). We found that peak Ptn expression correlates with periods of synaptogenesis and synaptic maturation (Figure 1B).…”
Section: Ptn Expression Is Developmentally Regulated and Is Decreased...mentioning
confidence: 99%
“…Our experiments were conducted in juvenile mice (between P21-P28). Although the dendritic branch structure is static after this age (Koleske, 2013, Richards et al, 2020, it is possible that changes in channel composition dampen the effects of dendritic branch structure on excitability. We show that such effects are possible with compartment models (Figure 7F), and it is known that changes in dendritic excitability can occur as a result of synaptic plasticity induction (Frick et al, 2003, Frick et al, 2004, Losonczy et al, 2008.…”
Section: Implications For Synaptic Plasticitymentioning
confidence: 99%